Meu professor inesquecível: um estudo sobre as características da atuação do professor de educação física - Ferrari, Ana Lúcia de Sant'Ana (2007)
The present investigation is focused on Physical Education College professors from their former students point of view. The proposed question for this study was the following: What are the characteristics of professors performance that left positive marks on Physical Education College former students? The data were collected from interviews with four Physical Education College former students from a private university in São Paulo state. The analysis of the content was made upon six cathegories: reasons for choosing that profession, the remembered professor, the professor s personal characteristics, the professor s performance, marks that were left on personal and professional student s life. The reference to the analysis was Henri Wallon s theory of development, highlighting affectivity, which guides the teaching-learning process. The results showed that the professors who left marks on their students were the ones who developed a positive mediation between the student and the content taught, by showing their knowledge of the subject, their ability to turn that knowledge into teaching, passion for teaching and respect for their students. Characteristics like good-temper, kindness and devotion were also pointed out by the interviewed students, but the most emphasized one was the professor s knowledge of the subject. The results of this investigation will provide subsidies for professors performance and propositions for Physical Education professor s education